2016
DOI: 10.1007/s11356-016-6860-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hospital laundry wastewater by UV/H2O2 process

Abstract: Hospitals consume a large volume of water to carry out their activities and, hence, generate a large volume of effluent that is commonly discharged into the local sewage system without any treatment. Among the various sectors of healthcare facilities, the laundry is responsible for the majority of water consumption and generates a highly complex effluent. Although several advanced oxidation processes (AOPs) are currently under investigation on the degradation of a variety of contaminants, few of them are based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…In this sense, increasing the temperature in Fenton oxidation could allow the treatment of the hospital wastewater in a single step as it has been proved to lead to a significant improvement of the oxidation rate and the mineralization percentage as well as a more efficient use of H 2 O 2 [28]. The proposed approach would allow taking advantage of the heat energy contained in the laundry stream since the laundering procedures imply the use of high temperature (>70 ºC) to assure disinfection of the hospital textiles [29][30][31], being responsible for 50% of hospitals water consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, increasing the temperature in Fenton oxidation could allow the treatment of the hospital wastewater in a single step as it has been proved to lead to a significant improvement of the oxidation rate and the mineralization percentage as well as a more efficient use of H 2 O 2 [28]. The proposed approach would allow taking advantage of the heat energy contained in the laundry stream since the laundering procedures imply the use of high temperature (>70 ºC) to assure disinfection of the hospital textiles [29][30][31], being responsible for 50% of hospitals water consumption [32].…”
Section: Introductionmentioning
confidence: 99%
“…In environmental studies of real effluents, sample degradation is a matter of great concern when long periods of experimentation are needed to determine the best conditions for a treatment process. 7 In this sense, in addition to carrying out the experiments with a maximum of 24 hours after collection, each procedure and control parameter was repeated five times. The mean value and standard deviation of the five repetitions were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being highly polluting, inside a hospital, these effluents can be treated and reused at a non-potable level and have the potential to reduce water consumption in these institutions, as well as avoid their direct disposal in the untreated urban sewage network. 7 For this purpose, several composite samples were submitted to C/F under different conditions of pH and dosage of C-Fs. The results of the study are shown in was observed that the effluents studied by Martins 164 have different characteristics -they can contain four times more oils and greases than those from hospital laundries.…”
Section: Evaluation Of the Coagulation And Flocculation Processmentioning
confidence: 99%
“…5,6 In a context in which water scarcity combined with surface water pollution represents one of the major problems today, the multiple activities that take place in health facilities, both medical and auxiliary, generate an exorbitant volume of wastewater, [7][8][9][10][11] with varying compositions, different types, and concentrations of different pollutants may be being released into the environment [11][12][13][14][15][16][17][18][19] through disposal without treatment in public sewage. 7,18,[20][21][22][23][24][25][26][27] Wastewater generated from health facilities poses a potential threat to the environment and public health due to the discharge of toxic chemicals that affect various aquatic species. 10,[28][29][30][31][32][33][34] In this sense, hospital effluents are 5 to 15 times more toxic than urban effluents.…”
Section: Introductionmentioning
confidence: 99%